Isomers of Poly Aminophenol: Chemical Synthesis, Characterization, and Its Corrosion Protection Aspect on Mild Steel in 1 M HCl. (17th March 2014) - Thenmozhi, G.; Arockiasamy, P.; Santhi, R. Jaya
Abstract : The oxidative chemical polymerizations of three isomers of aminophenol, ortho, meta, and para (PoAP, PmAP, and PpAP), were performed in aqueous HCl using ammonium persulfate as an oxidant at 0–3°C. The synthesized polymers were characterized by employing elemental analysis, GPC, UV-VIS-NIR, FT-IR, XRD, and TGA. The corrosion inhibition effect of these three polymers on mild steel in 1 M HCl solution was studied by using electrochemical techniques such as potentiodynamic polarization and electrochemical impedance spectroscopy. These measurements reveal that the inhibition efficiency obtained by these polymers increased by increasing their concentration. The inhibition efficiency follows the order PpAP > PoAP > PmAP. The results further revealed that PpAP at a concentration of 250 mg/L furnishes maximum inhibition efficiency (96.5%). Polarization studies indicated that these three polymers act as the mixed type corrosion inhibitors.